T-Cell Non-Hodgkin Lymphoma of the Ileum Presenting as Perforation and Peritonitis: A Case Report - Tian, Yong; Li, Chuanfang; Tian, Rusong; Tian, Qingming; Qiao, Song (Frontiers in Surgery, 2022)
Background Non-Hodgkin lymphoma (NHL) of the ileum, presenting as perforation and peritonitis, is a rare disease, derived from intestinal intraepithelial T lymphocytes. The degree of malignancy is extremely high. The pathogenesis of ileal perforation caused by NHL remains unclear, as well as the chromosome and immune system abnormalities, which may be related to NHL, and are indistinguishable from other benign and malignant conditions and are clinically nonspecific. Case Report We describe an 84-year-old man with abdominal pain for 4 days, which was aggravated for 3 h. The pain was in the upper abdominal region and was initially considered to be due to gastrointestinal perforation. He had persistent insidious pain, accompanied by nausea, vomiting, and fever. Physical examination indicated that the patient had pain all over the abdomen; also, rebound pain and muscle tension, and bowel sounds were reduced on auscultation. An abdominal CT scan showed free gas in the abdominal cavity. The patient was diagnosed with peritonitis due to hollow viscus perforation. A prompt exploratory laparotomy was performed. Intraoperative findings showed perforations in the ileum that are approximately 40 cm from the ileocecal region, which were 3–8 mm in size. A segmental distribution was observed, and the intestinal contents overflowed with purulent discharge around the perforation surface. Resection and ileostomy were performed, and the clinical histopathological examination confirmed T-cell lymphoma. The patient was advised to visit the Oncology Department for further chemotherapy. Conclusion Timely emergency surgery is the key to the treatment of ileal perforation caused by T-cell lymphoma. Resection and ileostomy were performed as intervention measures, and subsequent histopathological examination manifested T-cell lymphoma.